The signaling effect of tax policy - Francesca Barigozzi; Bertrand Villeneuve (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
The paper focuses on the signaling value of a tax when agents are less informed on the effect of their consumption than the policy-maker. When he chooses the tax, the policy-maker optimizes both the incentive effect and the effect on beliefs. We show that optimal taxes under symmetric information are not implementable under asymmetric information. The tax distortion required for credibility depends on the marginal cost of public funds and brings to undertaxation.
Keywords: 330; Steuerpolitik; Signalling; Optimale Besteuerung; Wohlfahrtsanalyse; Theorie